2010
DOI: 10.1074/jbc.m110.123497
|View full text |Cite
|
Sign up to set email alerts
|

p21-activated Kinase 4 Phosphorylation of Integrin β5 Ser-759 and Ser-762 Regulates Cell Migration

Abstract: Modulation of integrin ␣v␤5 regulates vascular permeability, angiogenesis, and tumor dissemination. In addition, we previously found a role for p21-activated kinase 4 (PAK4) in selective regulation of integrin ␣v␤5-mediated cell motility (Zhang, H., Li, Z., Viklund, E. K., and Strömblad, S. (2002) J. Cell Biol. 158, 1287-1297). This report focuses on the molecular mechanisms of this regulation. We here identified a unique PAK4-binding membrane-proximal integrin ␤5-SERS-motif involved in controlling cell attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 65 publications
2
43
2
Order By: Relevance
“…3). It has also been suggested that PAK4 plays a role in angiogenesis through phosphorylation of the integrin αvβ5, which affects endothelial cell motility and permeability 84 .…”
Section: Pak and Angiogenesismentioning
confidence: 99%
“…3). It has also been suggested that PAK4 plays a role in angiogenesis through phosphorylation of the integrin αvβ5, which affects endothelial cell motility and permeability 84 .…”
Section: Pak and Angiogenesismentioning
confidence: 99%
“…PAK4-Cdc42 interaction has also been shown to support redistribution of PAK4 to the Golgi compartment in porcine endothelial cells (Abo et al, 1998). In addition, PAK4 also signals through LIMK1 and stabilizes actin–myosin filaments (Dan et al, 2001), while PAK4 phosphorylation of integrin β5 on Ser759 and Ser762 promotes cell migration (Li et al, 2010b). Both PAK4 and PAK5 phosphorylate p120-catenin on Ser288 for cytoskeleton reorganization (Wong et al, 2010).…”
Section: Paks and Cytoskeleton Remodelingmentioning
confidence: 99%
“…PAK4 phosphorylates the cytoplasmic tail of β-5 integrin, which subsequently has important implications in cell adhesion and migration. 54 Phosphorylation of p120 and β-5 integrin by the group A Paks has not yet been reported. Group A Paks are also implicated in cell adhesion, however, and one important mediator is GIT1.…”
Section: Pak Kinases and Cytoskeletal Organizationmentioning
confidence: 99%